Around Mind Reflections": Exploração da sensação de presença no contexto de instalações artísticas interativas - Gonçalo João Figueira dos Santos (2019)
This dissertation establishes relationships between the terms presence sensation,the perceptual system and site-specific immersive environments. In a practice-basedresearch format, it is intended to design an immersive environment, through theconstraints of the space itself, using a parametric loudspeaker. Thus, we intend toinvestigate possible factors that may influence the feeling of presence and our perceptualsystem.